Integrative Learning Model in Pediatric and Sorches on Athletics Materials with Science Education Biology Materials for Junior High School Students - Elbadiansyah; Masyni; Muhamad Rohadi; Agung Sugiarto (Postgraduate, University of Mataram, 2024)
This research aims to produce an integrative learning model for junior high school students that is suitable for use. The integrative learning model is expected to be used by physical education teachers in teaching and learning activities. This development research was carried out by adapting the following research steps: data collection, analysis of the information collected, development of initial product draft, expert validation and revision, small-scale trials and revisions, large-scale field trials and revisions, and final product creation. A small-scale trial was carried out on 25 students of SMP Negeri 1 Samarinda. Large-scale trials were carried out on 31 students of SMP Negeri 2 Samarinda, SMP Negeri 3 Samarinda, and SMP Negeri 4 Samarinda. Data collection instruments are interview guides, field notes, validation value scales, teacher participation, student responses, performance tests and knowledge tests. Data analysis uses qualitative and quantitative descriptive analysis. The results of this research are in the form of a guidebook containing syntax (steps), assessment forms, 6 integrative games, and plans for implementing appropriate and effective learning.